2008
DOI: 10.1007/s11104-008-9767-1
|View full text |Cite
|
Sign up to set email alerts
|

Physiological N response of field-grown maize hybrids (Zea mays L.) with divergent yield potential and grain protein concentration

Abstract: Fertilizer N availability impacts photosynthesis and crop performance, although cause-effect relationships are not well established, especially for field-grown plants. Our objective was to determine the relationship between N supply and photosynthetic capacity estimated by leaf area index (LAI) and single leaf photosynthesis using genetically diverse fieldgrown maize (Zea mays L.) hybrids. We compared a high yield potential commercial hybrid (FR1064 x LH185) and an experimental hybrid (FR1064 x IHP) with low y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(85 citation statements)
references
References 30 publications
4
73
0
8
Order By: Relevance
“…There was a strong correlation between NUE and NUE-PY (r = 0.79, Table 4), suggesting that NUE-PY may be considered as a component of NUE in plant breeding. The effects of NUE on both grain quantity and quality characteristics need to be considered (Peterson et al 1992;Uribelarrea et al 2009). Some genotypes which responded strongly to N fertilisation, were low yielding and had low NUE at low N supply (for example, Kord CL Plus at PIN 10, Axe at CUM 11, Grenade at ROS 11).…”
Section: Discussionmentioning
confidence: 99%
“…There was a strong correlation between NUE and NUE-PY (r = 0.79, Table 4), suggesting that NUE-PY may be considered as a component of NUE in plant breeding. The effects of NUE on both grain quantity and quality characteristics need to be considered (Peterson et al 1992;Uribelarrea et al 2009). Some genotypes which responded strongly to N fertilisation, were low yielding and had low NUE at low N supply (for example, Kord CL Plus at PIN 10, Axe at CUM 11, Grenade at ROS 11).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen is most yield limiting nutrient, its stress reduces grain yield by delaying plant growth and development. Maize is usually considered to have a high soil fertility requirement to achieve maximum yield (Uribelarrea et al, 2009). Thus, it require large quantities of N for optimal growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported positive effects of N fertilization on corn plant biomass, photosynthesis and grain yield (Fabrizzi et al, 2005;Ma et al, 2005;Uribelarrea et al, 2009).…”
Section: Introductionmentioning
confidence: 99%